THE DISCOURSE OF HUMAN – INSECT COEXISTENCE IN FRANK HERBERT’S THE GREEN BRAIN - Kholishoh , Nur Diana; Tirmidi, Tirmidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Frank Herbert’s The Green Brain challenges readers to rethink the human-nature relationship. This article examines how the novel’s narrative and discourse address ecological issues, using linguistic, narrative, and intertextual analysis to reveal non-human subjectivities as a counter-discourse. Using Kristeva’s discourse analysis accompanied by Mandler and Johnson’s story grammar and Gee’s intertextual analysis techniques, it highlights how ignorance of species benefits leads to neglect. The study finds that due to the lack of knowledge on other species’ benefits to humans, people tend to neglect the importance of other species’ existence. It also elaborates that overpopulation sometimes forces people to exterminate others’ existence.